Inflated Expectations and Commodity Prices: Evidence from Kazakhstan - Victoire Girard; Alma Kudebayeva; Gerhard Toews (Global Labor Organization (GLO), 2020)
We document that an oil price boom triggers dissatisfaction with one's income, and confirm that this is not driven by changes in real economic conditions. Unique data from Kazakhstan allows us to exploit time, sectoral and spatial variation to identify the impact of the recent oil boom on reported satisfaction with income. Oil related households – whose heads are employed in the private sector of the oil rich districts – report a decrease in satisfaction with their income during the boom compared to other households (whose heads work in other sectors and/or districts). The estimated drop in satisfaction is statistically and economically significant: doubling the price of oil decreases satisfaction with income by one-tenth of a standard deviation in satisfaction. We discuss different interpretations of this drop in satisfaction. The most plausible explanation of our findings is that the changes people observe during the boom seem to fall short of their aspirations. Our results call for devoting more attention to the dynamic of satisfaction, not only during resource busts, but also during resource booms.
Keywords: J52; N55; Q33; Q34; 330; Expectations; Labor Conflict; Oil boom; Resource Curse; Satisfaction